Policy Trade-Offs in Building Resilience to Natural Disasters : The Case of St. Lucia - Cantelmo, Alessandro; Bonato, Leo.; Melina, Giovanni; Salinas, Gonzalo (Washington, D.C. : International Monetary Fund, 2019)
Resilience to climate change and natural disasters hinges on two fundamental elements: financial protection -insurance and self-insurance- and structural protection -investment in adaptation. Using a dynamic general equilibrium model calibrated to the St. Lucia's economy, this paper shows that both strategies considerably reduce the output loss from natural disasters and studies the conditions under which each of the two strategies provides the best protection. While structural protection normally delivers a larger payoff because of its direct dampening effect on the cost of disasters, financial protection is superior when liquidity constraints limit the ability of the government to rebuild public capital promptly. The estimated trade-off is very sensitive to the efficiency of public investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet